The UPeXplorer a three-dimensional map of the UP Diliman campus which integrates the global communications capability of the internet and the interactive environment of virtual reality using VRML - Laconsay, Rommel U. (1997)
For centuries, man had always thought of ways of communicating effectively. As we occupied more space and became more scattered, verbal face-to-face communication wasn't just enough This had led man to invent writing as another means of communication. The inventions and development of the telephone, radio, television and other media were also manifestations of our desire to effectively express our ideas and acquire information from others.